Secretory mitophagy: an extracellular vesicle-mediated adaptive mechanism for cancer cell survival under oxidative stress - Gade, Purva V.; Rivera, Angela Victoria Rojas; Hasanzadah, Layla; Strompf, Sofie; Philipson, Thomas Raymond; Gadziala, Matthew; Tyagi, Atharva; Bandam, Arnav; Gabbireddy, Rithvik; Kashanchi, Fatah; Haymond, Amanda; Liotta, Lance A.; et al. (Frontiers in Cell and Developmental Biology, 2025)
Mitophagy is a critically important survival mechanism in which toxic, aged, or defective mitochondria are segregated into mitophagosomes, which shuttle the damaged mitochondrial segments to the lysosome and proteasome for destruction. Cancer cells rely on mitophagy under conditions of high oxidative stress or increased energy demand. Oxidative stress can generate a large volume of damaged mitochondria, overwhelming lysosomal removal. Accumulated damaged mitochondria are toxic and their proper removal is crucial for maintaining mitochondrial health. We propose a new cancer cell mechanism for survival that is activated when the demand for segregating and eliminating damaged mitochondria exceeds the capacity of the lysosome or proteasome. Specifically, we show that tumor cells subjected to oxidative stress by carbonyl cyanide-3-chlorophenylhdrazone (CCCP) eliminate damaged mitochondria segments by bypassing the lysosome to export them outside the cell via extracellular vesicles (EVs), a process termed “secretory mitophagy”. PINK1, the initiator of mitophagy, remains associated with the damaged mitochondria that exported in EVs. Using several types of cancer cells, we show that tumor cells treated with CCCP can be induced to switch over to secretory mitophagy by treatment with Bafilomycin A1, which blocks the fusion of mitophagosomes with lysosomes. Under these conditions, an increased number of PINK1 + EVs are exported. This is associated with greater cell survival by a given CCCP dose, enhanced mitochondrial ATP production, and reduced mitochondrial oxidative damage (membrane depolarization). Our data supports the hypothesis that secretory mitophagy is a previously unexplored process by which cancer cells adapt to survive therapeutic or hypoxic stress. Ultimately, our findings may inform new prevention strategies targeting pre-malignant lesions and therapeutic approaches designed to sensitize tumor cells to oxidative stress-inducing therapies.